Tinjauan Yuridis Pemekaran Wilayah Daerah Provinsi Berkaitan Dengan Wacana Pemekaran Provinsi Nusa Tenggara Timur (NTT) - Ama, Jefrianus Tamo (Media Hukum Indonesia (MHI), 2025)
In principle, the formation of the expansion of the provincial region, according to the 1945 Constitution of the Republic of Indonesia in Article 18B (1) explicitly states that the Unitary State of the Republic of Indonesia consists of provincial regions, districts/cities that have regional autonomy. The formation of new provinces is an implementation of the principle of decentralization in the 1945 Constitution. Regional expansion is a process of forming new autonomous regions from an existing region. The formation of new regional expansion is based on the principle of decentralization which applies the division of authority to regulate the household of the region itself. The discourse on the Expansion of the Province of East Nusa Tenggara is an aspiration from the community, this is only a discourse or issue that was then responded to by several politicians and members of the People's Representative Council of the Republic of Indonesia. For this reason, the expansion of the provincial region is based on Law No. 23 of 2014 concerning Regional Government and Implementing Regulations, Government Regulation of the Republic of Indonesia Number 78 of 2007 concerning Procedures for the Formation, Elimination, and Merger of Regions. In this regulation as the implementer of Law No. 23 of 2014, which includes the procedures for implementation, mechanisms, and procedures for the formation of regional areas. In this study, the author uses a normative legal approach research, and sociological analysis based on existing secondary data, namely from: Books, magazines, journals, newspapers, websites, as a benchmark for this author or author.